Patient Perspectives on Acute Exacerbations of Chronic Rhinosinusitis: A Qualitative Study. (29th January 2023) - Walker, Victoria; Trope, Michal; Tichavakunda, Antar A.; Speth, Marlene M.; Sedaghat, Ahmad R.; Phillips, Katie M.
Abstract: Objective: Acute exacerbations of chronic rhinosinusitis (AECRS) are currently defined as a transient worsening of symptoms that return to baseline. This definition is narrow and can only be made retrospectively. The literature has studied this phenomenon from the physician perspective, yet a key stakeholder's—the patient's perspective is not well elucidated in the literature. To understand AECRS from the patient's perspective, we performed this study to further clarify this phenomenon. Study Design: Basic qualitative study via patient interviews using constant comparative methodology was conducted. Setting: Tertiary care academic center. Methods: Two of the authors served as coders, and via group discussion, a common codebook was created and used to identify recurrent themes. The themes were analyzed for meaning and conclusions were summarized. Results: Ten interviews were conducted with chronic rhinosinusitis (CRS) patients. Recurring themes included the following: (1) patients identify with the term flare or sinus infection more than exacerbation ; (2) consistent with the current definition, patients identify AECRS by worsening sinonasal symptoms but also relate secondary symptoms, including poor sleep, fatigue, exacerbation of lower respiratory tract symptoms, and malaise to AECRS; and (3) patients are greatly affected by AECRS via decreased quality of life (QOL), worsening of general health, and decreasing productivity. Conclusion: Beyond worsening of sinonasal symptoms, the concept of AECRS reflects a more complex construct to patients with associated extranasal symptoms and systemic manifestations. In addition, AECRS have a large impact on patients, and therefore, understanding this component of CRS is pivotal in improving disease control and QOL in this patient population.